Kvantitativni podatki o besedotvornih modelih in priponskih nizih izmedmetnih tvorjenk v Besednodružinskem slovarju slovenskega jezika za iztočnice na b - Stramljič Breznik, Irena (Slovenski jezik, 2024)
This article discusses the older and newer semantic typologies of interjections and their word formation properties – in relation to both the formation of other interjections and other parts of speech. We show how the Word Family Dictionary of the Slovene Language, which contains within the individual entries all possible word formation sequences at different levels, can be used for morphotactic research in Slovene. This article provides a statistical analysis of the word formation sequences derived from all nineteen interjection entries in the Word Family Dictionary of the Slovene Language. The analysis focuses on different stages in word formation, the length of suffix chains, the ability of suffixes to combine in suffix chains and the number of different multilevel derivations as well as their frequency in the metaFida corpus.
Keywords: besedotvorje; derivatives; interjection; izmedmetni stopenjski priponski niz; medmet; morfotaktika; morphotactics; Slovene language; slovenščina; tvorjenke; word formation; word formation sequences of the interjection